# Discrete Math

posted by .

Justifying your conclusions (you could also use examples in order to illustrate your results).

What can you say about the sets A and B if we know that:

1. A ∪ B = A
2. A ∩ B = A

Thanks for any helpful replies :)

• Discrete Math -

1. A∪B = A
=> x∈B -> x∈A
=> B⊆A

2. A∩B = A
=> x∈A -> x∈B
=> A⊆B

Now
B⊆A ∧ A⊆B
means what?

## Similar Questions

1. ### Math

1) Given the universal set U = {1, 2, 3, 4, 5, 6, 7, 8, 9, 10} and sets A = {2, 3, 4, 6}, B = {5, 6, 7, 8, 10}, C = {6, 8, 10}, and D = {1, 2, 7, 9}, answering the following: 1- a) What is A ∪ C?
2. ### discrete math help please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
3. ### discrete math help please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
4. ### math help

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
5. ### URGENT! discrete math help please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
6. ### URGENT HELP WITH DISCRETE MATH PLEASE

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
7. ### math. Somebody help urgently please

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
8. ### math

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
9. ### math

1. for any sets X and Y, we define the symmetric difference X ∆Y by: X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove the following: -for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ …
10. ### Math - sets

Suppose A, B, and C are sets. In at least one of the following situations, one can conclude that A = B. Identify those cases where this conclusion does apply. (i) A ∪ C = B ∪ C A={1,2},A={1,2}, B={2,3}B={2,3} and C={1,2,3}.C={1,2,3}. …

More Similar Questions